Tinjauan Literatur Metode Penilaian Hidrasi pada Populasi Lansia: Kelebihan dan Kekurangan - Sheila Amara Putri; Farapti Farapti (Universitas Airlangga, 2023)
Background: The elderly population is vulnerable to hydration problems, which can have adverse effects on their health. Accurate and reliable hydration assessment methods are crucial for effective detection, monitoring, and management of hydration status in the elderly. However, there is currently no consensus on the optimal method. Objectives: This literature aims to analyze the hydration assessment methods used in the elderly population and evaluate their strengths and limitations. Methods: This study gathered data from relevant literature and research articles obtained from journals in databases such as PubMed, Google Scholar, and Science Direct. Articles were searched using keywords such as Hydration Assessment, Hydration Markers, and (elderly OR older). Data sources included publications from official websites and research journals. The literature review process involved selecting the review topic, searching for relevant articles, and analyzing and synthesizing the available literature. Discussion: Several hydration assessment methods in the elderly include biochemical parameters, clinical signs and symptoms, bioimpedance analysis (BIA), and ultrasonography. However, no single method can provide a comprehensive picture of dehydration status in the elderly. Conclusions: When selecting an appropriate assessment method, factors such as assessment goals, strengths, limitations, sensitivity, specificity, cost, equipment availability, ease of use, and time required need to be considered. By considering these factors, researchers can choose the most suitable hydration assessment method for the elderly population, thereby obtaining accurate and relevant information for proper management and care.